Interaction of Sub-Base with Structure Considering Lateral Forces : A Review - Agrawal, Mayank; Mire, Anisha; Singh, Lokesh (International Journal of Scientific Research in Civil Engineering, 2020)
Lateral forces are now a days considered as the most important load to be applied for designing a tall structure. around the world it has different provisions as per country code but the factor is same to reisst lateral forces and to analyze the structure for concern region zone and base shear. for seismic analysis the most important part to be consider is soil. As soil is the main part from where shakes appears and applied to the structure. In this paper we are presenting literature review of publications and journals related to interaction of structure and sub base material also reviewing analysis tools related to structural analysis.
Keywords: Structure Analysis; Soil Interaction; Analysis Tool; Materials; Forces; Moment; Deflection